Penerapan Teknik Pembelajaran Berbasis Masalah dalam Layanan Klasik untuk Meningkatkan Rasa Percaya Diri - Fadhila, Nida; Wastuti, Sri Ngayomi Yudha; Astuti, Sri (Yayasan Amanah Nur Aman, 2025)
Self-confidence is an important aspect for humans. This study was conducted with the aim of examining the implementation of the Problem-Based Learning technique to enhance the self-confidence of Grade XI F-5 students at SMA Negeri 10 Medan. The research was carried out in class XI F-5, which consisted of 32 students. This study employed the Guidance and Counseling Action Research (PTBK) method, conducted over two cycles. The type of research used was qualitative descriptive analysis, describing both the process during and after the intervention. Based on evaluation data, the results showed that the implementation of Problem-Based Learning through classical services can improve self-confidence among students in class XI F-5. Self-confidence is a psychological condition in students that manifests as a belief in their own abilities to take action in order to achieve goals. In the learning process, self-confidence is crucial to be nurtured and enhanced so that students are able to make decisions for their future. This research was conducted to assess the level of students' self-confidence and to test the effectiveness of the Problem-Based Learning technique through classical services in enhancing students' confidence.